Case Report of the surgical management of small bowel and colonic ischaemia associated with Anorexia Nervosa binge/purge subtype. (2016) - Foran, Ann T.; Clancy, Cillian; Gorey, Tom F.
Highlights: Anorexia nervosa is common, it has two subtypes; restrictive and binge/purge. Ischaemic bowel associated with anorexia nervosa is rare but potentially life-threatening. The mechanism of ischaemic bowel in anorexia nervosa has not been fully elucidated. This condition should be highlighted as it has a high associated mortality. Prompt involvement of radiology and surgery appears pivotal to outcome. Abstract: Introduction: Anorexia Nervosa affects up to 1% of the population and can present with binge/purge episodes. A paucity of literature exists regarding small bowel and colonic ischaemia relating to this common condition. We report our own experience and management of a patient with anorexia nervosa binge/purge subtype with small bowel and colon ischaemia and review existing cases in the literature. Presentation of case: A 32 year old female self-presented to the emergency department complaining of abdominal pain, abdominal distension and vomiting on a background history of binge/purge subtype eating disorder, following consumption of a large amount of carbohydrates. Computed tomography (CT) of the abdomen was performed urgently which revealed extensive pneumatosis involving the stomach and its draining veins with evidence of extensive portal venous gas. A right hemicolectomy followed by re-look laparotomy in 48 h with resection of jejunum, jejunojejunal anastomosis and end-ileostomy was performed with a successful outcome. Discussion: Anorexia nervosa can be a potentially life-threatening disease, with rates of death 10–12 times that of the normal population. Ischaemic bowel is a rare potential complication, with mortality rates of up to 80% having been reported prior to this case. Although the exact mechanism remains to be elucidated, gastric dilation, abnormal digestive motility, and faecal impaction appear to contribute, on a background of impaired blood supply. Conclusion: Clinicians need to exhibit a high index of suspicion for patients with abdominal pain on the background of an eating disorder, particularly in the context of suspected recent refeeding/binge eating. Prompt involvement of appropriate radiology and surgery input are pivotal to outcome.